The U.S. Manufacturing Recovery : Uptick or Renaissance? - Celasun, Oya.; Di Bella, Gabriel; Mahedy, Tim.; Papageorgiou, Chris (Washington, D.C. : International Monetary Fund, 2014)
The notable rebound of U.S. manufacturing activity following the Great Recession has raised the question of whether the sector might be experiencing a renaissance. Using panel regressions, we find that a depreciating real exchange rate, an increasing spread in natural gas prices between the United States and other G-7 countries, and in particular decreasing unit labor costs have had a positive impact on U.S. manufacturing production. While we find it unlikely for manufacturing to become a main engine of growth in the United States, we find that U.S. manufacturing exports could provide nonnegligible growth opportunities going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet